2015
DOI: 10.1007/s40030-015-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Flexural Strength of Concretes Containing Silica Fume and Styrene-Butadiene Rubber (SBR) with an Empirical Model

Abstract: In the flexural test, the theoretical maximum tensile stress at the bottom fiber of a test beam is known as the modulus of rupture or flexural strength. This work deals with the effects of Silica Fume and Styrene-Butadiene Latex (SBR) on flexural strength of concrete. An extensive experimentation was carried out to determine the effects of silica fume and SBR on flexural strength of concrete. Two water-binder ratios and several percentages of silica fume and SBR were considered. Abrams' Law, which was original… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The work provided an impact of integrated SBR latex on the microstructure, and chloride bonding behavior of Portland cement mortar [41].In [42][43] SPR examined SBR-modified reinforced concrete beams and it showed significant improvement in the flexural strengths of modified concrete. In [44], as noted in previous research, the bending strength of concrete with 5% SBR significantly increases with CS, and replacing cement with SF improves the F up to 7.5%. The effect of applying SBR polymer is studied on concrete in conjunction with fly ash and SF [45].…”
Section: Literature Reviewsupporting
confidence: 83%
“…The work provided an impact of integrated SBR latex on the microstructure, and chloride bonding behavior of Portland cement mortar [41].In [42][43] SPR examined SBR-modified reinforced concrete beams and it showed significant improvement in the flexural strengths of modified concrete. In [44], as noted in previous research, the bending strength of concrete with 5% SBR significantly increases with CS, and replacing cement with SF improves the F up to 7.5%. The effect of applying SBR polymer is studied on concrete in conjunction with fly ash and SF [45].…”
Section: Literature Reviewsupporting
confidence: 83%
“…The concrete flexural strength was notably enhanced when steel fibers and silica fume were employed simultaneously, according to M. Nili and V. Afroughsabet [ 84 ]. M. Shafieyzadeh discovered that substituting up to 7.5% of the cement with silica fume increases the flexural strength of concrete by 15% [ 85 ]. M. Shmlls et al found that the combined dosage of silica fume and fly ash enhanced the strength properties of concrete [ 86 ].…”
Section: Data Descriptionmentioning
confidence: 99%
“…The highest value of exural strength was at AAM VII with the highest M content, namely 9.5 MPa. Some other studies also con rmed the modi cation of exural strength by micro-silica [21] which is due to its pozzolanic behavior and high content of silica that improves the bond of the paste and increases the strength and durability [22] EDS test was conducted on two sample types AAM-IV and AAM-VII. EDS determines the chemical composition of the material.…”
Section: Mechanical Properties Of Hardened Mortarmentioning
confidence: 99%